Beyond the Rhetoric: Moving from Exclusion, Reaching for Inclusion in Canadian Schools - Sefa Dei, George J.; James, Irma Marcia (Alberta Journal of Educational Research, 2002)
This article is informed by the findings of a three-year research study in Ontario schools in order to understand the factors and forces that make for students' engagement and disengagement in schools. Although research has sought to understand the processes that contribute to some students feeling a sense of marginality and disconnectedness in their schools, we have also paid attention to exemplary practices of inclusive schooling in educational settings. Specifically, in this article we examine educational practices that engender exclusion or inclusion, particularly of racially marginalized students in Euro-American or Canadian contexts. We develop an analysis that uncovers the connection between "inclusionary and exclusionary" practices of schooling. "Inclusivity" moves beyond mere classroom presence of minorities or superficial attempts at multiculturalism: students may feel disempowered and therefore excluded as far as actual classroom practices are concerned (e.g., teaching, sharing knowledge). Moving from exclusion means identifying students' own narrative accounts of marginality and subordination that result in feeling left out. Reading for inclusion means interrogating strategies initiated by schools, students, educators, parents, and local communities to counteract the marginalization of disadvantaged and racial minority youths. Our aim in this article is to use available research information to encourage the wider application of effective inclusive practices to improve learning outcomes for all youth.